5 kHz Transcranial Alternating Current Stimulation: Lack of Cortical Excitability Changes When Grouped in a Theta Burst Pattern - Kunz, Patrik; Antal, Andrea; Hewitt, Manuel; Neef, Andreas; Opitz, Alexander; Paulus, Walter (Frontiers in Human Neuroscience, 2017)
Background: Suprathreshold transcranial single pulse electrical stimulation (TES) is painful and not applicable in a repetitive mode to induce plastic after-effects. Objective: In order to circumvent this pain problem we applied here a 5 kHz transcranial alternating current stimulation (tACS) theta burst protocol with a field intensity of up to 10 mA to the primary motor cortex (M1). Furthermore, we were interested in finding out whether electrical theta burst stimulation (eTBS) is able to induce lasting after-effects on cortical plasticity. Methods: Three different eTBS protocols were applied at 5 mA in a sham controlled, double blinded cross-over design on the M1 region of seventeen healthy subjects during the first part of the study. The second study part consists of 3 different eTBS protocols ranging from 5 mA to 10 mA and 1 ms to 5 ms sinusoidal bursts, applied to the M1 region of fourteen healthy subjects. Results: We were able to apply all eTBS protocols in a safe manner, with only six subjects reporting mild side effects related to the stimulation. However, no eTBS protocol induced lasting effects on muscle- evoked potential (MEP) amplitudes when compared to sham stimulation. Significant inhibition of MEP amplitude was only seen in the lower intensity protocols as compared to baseline. Conclusion: eTBS is a safe method to apply high frequency tACS with up to 10 mA intensity. Future studies need to explore the parameter space to a larger extent in order to assure efficacy.